Antibiotic consumption and antibiotics occurrence into the environment: a case study of hospital in Metro, Lampung - Fahmi, Achmad Gus; Abidin, Zaenal; Kusmana, Cecep; Noor, Erliza (Current Research on Biosciences and Biotechnology, 2024)
Increased antibiotic consumption has exposed bacterial communities and environmental ecosystems to large amounts of antibiotic residues derived from the excretion of irrationally consumed antibiotics. This study provides an overview of antibiotic consumption patterns in hospital inpatients and the distribution of residues released into the environment. Medical record data was used to calculate the amount of consumption from hospital inpatients, and based on the type of antibiotics that have a DU90% value, ecotoxicological risk calculations were carried out to estimate the level of danger that occurs in the environment. A total of 27 types of antibiotics were prescribed, with a total consumption of 20504.42 Kg/year. Antibiotics such as ceftriaxone, cefixime, cefadroxil, and levofloxacin are the most widely used antibiotics based on medical record data. The results of estimating the release of antibiotic residues in wastewater obtained ecotoxicological risk values for algae, invertebrates, and fish greater than one (RQs>1). This condition indicates an ecotoxicological risk at the health facility site due to the release of antibiotic residues into the river water body from the WWTP outlet. The release of antibiotic residues into the water can result in ecosystem damage and pollution of the aquatic environment.